ANALISIS SISTEM INFORMASI MANAJEMEN BERBASIS KOMPUTER DALAM PROSES PENGAMBILAN KEPUTUSAN - Paul Eduard Sudjiman; Lorina Siregar Sudjiman (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2018)
Information System Computer-based management means that computers play an important role in a management information system. Organizational success is closely related to technical competence, organizational ability to carry out adaptions to the external and internal environment. Amid the rapid development of technology, the use of Management Information System is the right choice for processing quality information resources. The role of management requires the dissemination and use of efficient sources to achieve a goal, thus helping the management function with the receipt of information quickly and precisely. Then a good management information system is needed to support organizational goals. Management Information System that are accurate and effective, in reality are always related to the term computer-based or information processing based on computer. In each process information is needed which is partly generated by the management information system. Information generated by information system with special analysis is very useful for organizational needs and decisions taken at each level of management. Thus the purpose of the establishment of a management information system (SIM) is that the organization provides